Analysis of the dissolution of CH4/CO2-mixtures into liquid water and the subsequent hydrate formation via in situ raman spectroscopy - Li, Zheng; Holzammer, Christine; Braeuer, Andreas S. (Energies, 2020)
We report an experimental study for the investigation into the suitability of hydrate formation processes for the purification of methane (CH4) from carbon dioxide (CO2) at a sub-cooling temperature of 6 K and a pressure of 4 MPa. The experiments were conducted in a stirred batch reactor. Three different initial CH4/CO2 mixtures with methane fractions of 70.1 mol%, 50.3 mol%, and 28.5 mol% were tested. The separation efficiency was quantified by measuring in situ via Raman spectroscopy the ratios of CH4/CO2 in the gas mixture, the liquid water-rich phase before hydrate formation, and the solid hydrate phase after the onset of the hydrate formation. The results indicated that the main separation effect is obtained due to the preferential dissolution of CO2 into the liquid water-rich phase before the onset of the hydrate formation.
CRIS-Team Scopus Importer:2020-02-28
Keywords: Carbon dioxide; Gas hydrates; In situ Raman spectroscopy; Methane; Molar ratio

Determination Of Gas Hydrate Concentration In Water-CO2-Mixtures By Raman Spectroscopy - Holzammer, Christine; Brack, Monika; Bräuer, Andreas; Will, Stefan (European Meeting on Supercritical Fluids 2016, 2016)

Experimental Study of the Amount of Gas Hydrates in Macroscopic Single and Two Phase Water CO2 Mixtures - Holzammer, Christine; Will, Stefan; Braeuer, A. S. (Ninth International Conference on Gas Hydrates, ICGH9, 2017)

Experimental study of the influence of inhibitors on hydrogen bonds before the onset of gas hydrate formation - Holzammer, Christine; Finckenstein, A.; Bräuer, Andreas; Will, Stefan (11th International Symposium on Supercritical Fluids, 2015)

How Sodium Chloride Salt Inhibits the Formation of CO2 Gas Hydrates. - Holzammer, Christine; Finckenstein, Agnes; Will, Stefan; Bräuer, Andreas (Journal of Physical Chemistry B, 2016)
We present an experimental Raman study on how the addition of sodium chloride to CO2-hydrate-forming systems inhibits the hydrate formation thermodynamically. For this purpose, the molar enthalpy of reaction and the molar entropy of reaction for the reaction of weakly hydrogen-bonded water molecules to strongly hydrogen bonded water molecules are determined for different salinities from the Raman spectrum of the water-stretching vibration. Simultaneously, the influence of the salinity on the solubility of CO2 in the liquid water-rich phase right before the start of hydrate formation is analyzed. The results demonstrate that various mechanisms contribute to the inhibition of gas hydrate formation. For the highest salt concentration of 20 wt % investigated, the temperature of gas hydrate formation is lowered by 12 K. For this concentration the molar enthalpy and entropy of reaction become smaller by 50 and 20%, respectively. Concurrently, the solubility of carbon dioxide is reduced by 70%. These results are compared with data in literature for systems of sodium chloride in water (without carbon dioxide).

Influence of Sodium Chloride on the Formation and Dissociation Behavior of CO2 Gas Hydrates - Holzammer, Christine; Schicks, Judith M.; Will, Stefan; Bräuer, Andreas (Journal of Physical Chemistry B, 2017)

Investigation of the Influence of Thermodynamic Hydrate Inhibitors on the Development of Hydrogen Bonds in Hydrate Forming Systems by Raman Spectroscopy - Holzammer, Christine; Schicks, J; Will, Stefan; Bräuer, Andreas (Ninth International Conference on Gas Hydrates, ICGH9, 2017)

Investigation of The Influence of Thermodynamic Hydrate Inhibitors On The Properties of The Formed Hydrate Phase By Raman Spectroscopy - Holzammer, Christine; Schicks, J; Bräuer, Andreas; Will, Stefan (16th European Meeting on Supercritical Fluids, 2017)

Investigation of the Inhibition Effect of Thermodynamic and Kinetic Hydrate Inhibitors by Raman Spectroscopy - Holzammer, Christine; Bräuer, Andreas; Will, Stefan (Thermodynamik-Kolloquium 2016, 2016)

Raman Spectroscopic Study of the Effect of Aqueous Salt Solutions on the Inhibition of Carbon Dioxide Gas Hydrates - Holzammer, Christine; Braeuer, Andreas S. (Journal of Physical Chemistry B, 2019)
We present an experimental Raman study on the thermodynamic inhibition effect of different salts (NaCl, KCl, MgCl2, and CaCl2 from 2.5 to 11 wt %) on the formation of carbon dioxide gas hydrates. We performed the experiments in a high-pressure vessel with two phases: a water-rich phase and a CO2 -rich phase. We investigated the changes the inhibitors induce in the water-rich phase before the onset of hydrate formation. This includes a study of the change in molar reaction enthalpy between strongly and weakly hydrogen-bonded water and the decrease in solubility of carbon dioxide in water. Additionally, the growth mechanisms of carbon dioxide hydrates were investigated by determining the amount of solid hydrates formed and the reaction constant. The results show that the molar reaction enthalpy, the solubility of CO2 , and the amount of solid hydrates formed can be correlated with the effective mole fraction, whereas the reaction constant is not affected by the addition of salts. The decrease of the molar reaction enthalpy can be directly correlated with the equilibrium temperature of the gas hydrates.
CRIS-Team WoS Importer:2019-04-02